Conservation Design Assist: An Innovative Model to Integrate Conservation Expertise Within the Major Rehabilitation of Canada's Parliamentary Centre Block. (31st August 2020) - Bourdeau, James; Edgar, David; Koski, Eeva; Pohoriljakova, Ida; Mottus, Tania; Baird, Roger
ABSTRACT: The Centre Block in Ottawa is a classified federal heritage building housing Canada's parliament. Nearly a century after its formal opening, it closed in 2019 for a decade-long rehabilitation. This neo-gothic building will undergo complete structural, engineering, seismic and security upgrades while preserving its heritage character and materials. The lessons learned during the rehabilitation of other classified buildings in the Parliamentary Precinct have led the proponents of the Centre Block rehabilitation to adopt an integrated approach using 'Design Assist' to bring conservators directly into a critical role in the schematic design and design development. In a complex, fragile and highly visible project like this, the public perception of risk to heritage assets is unparalleled. This paper explores the ways in which Design Assist departs from the traditional Design Bid Build model to integrate 17 expert conservation specialisms with the architects and the construction authority. Case studies will be used to illustrate the value added by this innovative conservation-construction model.